ZmPUMP encodes a maize mitochondrial uncoupling protein that is induced by oxidative stress - Brandalise, Marcos; Maia, Ivan de Godoy [UNESP]; Borecký, Jirí; Vercesi, Aníbal Eugênio; Arruda, Paulo (Elsevier, 2003)
A cDNA clone (designated ZmPUMP) encoding an uncoupling protein (UCP) from maize (Zea mays) was identified by searching for homologous sequences among the expressed sequence tags of the GenBank database. The ZmPUMP cDNA contains a single open reading frame of 933 nucleotides encoding 310 amino acids. Several features identified the predicted ZmPUMP protein as a member of the mitochondrial UCP subfamily of mitochondrial carriers. Expression studies demonstrated that ZmPUMP is ubiquitously expressed in maize tissues and its transcript level is not altered in early stages of embryo germination. In contrast to known UCP genes, ZmPUMP is not responsive to cold stress. Instead its expression is increased in response to H 2O 2- or menadione-induced oxidative stress. © 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Maize; Mitochondria; Oxidative stress; Plant uncoupling mitochondrial protein; Amino acids; DNA; Genes; Oxidation; Proteins; Tissue; Reading frames; Plants (botany); Zea; Zea mays